Production of benzene/toluene/ethyl benzene/xylene (BTEX) via multiphase catalytic pyrolysis of hazardous waste polyethylene using low cost fly ash synthesized natural catalyst - Gaurh P.; Pramanik H. (My University, 2025)
The valuable aromatics benzene, toluene, ethyl benzene and xylene (BTEX) were effectively produced from waste polyethylene (PE) using fly ash synthesized catalyst. The BTEX yield was enhanced significantly using multiphase catalytic pyrolysis of polyethylene. Low cost natural catalyst was synthesized from fly ash (FA) in 5 different synthesized form i.e., fly ash in natural form (FAN), fly ash calcined at 600 °C (FA-600), 700 °C (FA-700), 800 °C (FA-800) and 900 °C (FA-900). The thermal and catalytic pyrolysis both were conducted in a specially designed semi-batch reactor at the temperature range of 500–800 °C. Catalytic pyrolysis were performed in two different phases within the reactor batch by batch systematically, keeping the catalyst in a liquid phase (A-Type) and liquid and vapor phase/multiphase (B-Type), respectively. The maximum liquid yield of 78.20 wt% was obtained at a temperature of 700 °C using FA-800 catalyst in A-type arrangement. Total aromatics (BTEX) of 10.92 wt% was obtained for thermal pyrolysis at a temperature of 700 °C. In contrary, the aromatic (BTEX) contents were significantly increased for the catalytic pyrolysis in both reactor arrangement A and B types, nearly doubled from 10.92 wt% (thermal pyrolysis) to 21.34 wt% for A-type and 22.12 wt% for B type/multiphase. The pyrolysis oil was characterized using GC-FID, carbon residue test and other fuel testing methods to evaluate the suitability of its end use and aromatic content. © 2018 Elsevier Ltd